2001
DOI: 10.1128/jvi.75.11.5084-5089.2001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Infection of Primary Tupaia Hepatocytes with Purified Human and Woolly Monkey Hepatitis B Virus

Abstract: The Asian tree shrew, Tupaia belangeri, has been proposed as a novel animal model for studying hepatitis B virus (HBV) infection. Here, we describe a protocol for efficient and reproducible infection of primary tupaia hepatocytes with HBV. We report that human serum interferes with HBV binding to the hepatocytes, thus limiting the maximum multiplicity of infection. Purification of HBV virions by gradient sedimentation greatly enhances virus binding and infectivity. Covalently closed circular DNA was clearly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 21 publications
4
91
1
Order By: Relevance
“…[21][22][23][24] We and others have demonstrated that primary Tupaia hepatocytes (PTHs) represent a convenient and suitable in vitro model to study HBV infection and replication. [25][26][27] In this study, we demonstrate that HBV core promoter mutants associated with fulminant hepatitis exhibit a phenotype in primary hepatocytes distinctly different from previous findings in hepatoma cell lines. This phenotype may have important implications for the understanding of the fulminant clinical course associated with mutations.…”
contrasting
confidence: 47%
“…[21][22][23][24] We and others have demonstrated that primary Tupaia hepatocytes (PTHs) represent a convenient and suitable in vitro model to study HBV infection and replication. [25][26][27] In this study, we demonstrate that HBV core promoter mutants associated with fulminant hepatitis exhibit a phenotype in primary hepatocytes distinctly different from previous findings in hepatoma cell lines. This phenotype may have important implications for the understanding of the fulminant clinical course associated with mutations.…”
contrasting
confidence: 47%
“…Further studies in the HBV and WHV system will have to establish whether mammalian core protein phosphorylation is essential for infectivity as well. The recently described infection of primary tupaia hepatocytes (34) might represent a suitable model to address this question. Interestingly, phosphorylation of capsid protein by capsid-associated kinase activities has also been suggested to play a key role during the early steps of HIV infection (35).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, primary human hepatocytes (PHHs) (Lempp et al, 2017;Ni and Urban, 2017;Shimura et al, 2017), HepaRG cells (Gripon et al, 2002;Schulze et al, 2012), and primary tupia hepatocytes (PTHs) (Kock et al, 2001;Ren and Nassal, 2001) are the main cell models used to study the early steps of HBV infection. PHHs, the natural host of HBV, are regarded as the ideal cellular model for HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of DMSO and polyethylene glycol 8000 (PEG8000) during the infection of PTHs does not significantly promote the infectivity of HBV (Weizsäcker and Roggendorf, 2005). In addition, human serum competes with HBV particles for binding to the cell membrane (Kock et al, 2001), leading to a reduced experimental confidence level. Novel HBV infection models are thus urgently needed.…”
Section: Introductionmentioning
confidence: 99%